Abrogation of histone deacetylases (HDACs) decreases survival of chronic myeloid leukemia cells: New insight into attenuating effects of the PI3K/c‐Myc axis on panobinostat cytotoxicity. (4th February 2021) - Zehtabcheh, Sara; Yousefi, Amir‐Mohammad; Salari, Sina; Safa, Majid; Momeny, Majid; Ghaffari, Seyed H.; Bashash, Davood
Abstract: Although the identification of tyrosine kinase inhibitors (TKIs) has changed the treatment paradigm of many cancer types including chronic myeloid leukemia (CML), still adjustment of neoplastic cells to cytotoxic effects of anticancer drugs is a serious challenge. In the area of drug resistance, epigenetic alterations are at the center of attention and the present study aimed to evaluate whether blockage of epigenetics mechanisms using a pan‐histone deacetylase (HDAC) inhibitor induces cell death in CML‐derived K562 cells. We found that the abrogation of HDACs using panobinostat resulted in a reduction in survival of the K562 cell line through p27‐mediated cell cycle arrest. Noteworthy, the results of the synergistic experiments revealed that HDAC suppression could be recruited as a way to potentiate cytotoxicity of Imatinib and to enhance the therapeutic efficacy of CML. Here, we proposed for the first time that the inhibitory effect of panobinostat was overshadowed, at least partially, through the aberrant activation of the phosphoinositide 3‐kinase (PI3K)/c‐Myc axis. Meanwhile, we found that upon blockage of autophagy and the proteasome pathway, as the main axis involved in the activation of autophagy, the anti‐leukemic property of the HDAC inhibitor was potentiated. Taken together, our study suggests the beneficial application of HDAC inhibition in the treatment strategies of CML; however, further in vivo studies are needed to determine the efficacy of this inhibitor, either as a single agent or in combination with small molecule inhibitors of PI3K and/or c‐Myc in this malignancy.